Compensatory saccade in the vestibular impaired monkey - Kojima, Yoshiko; Ling, Leo; Phillips, James O. (Frontiers in Neurology, 2023)
Introduction Loss of the vestibulo-ocular reflex (VOR) affects visual acuity during head movements. Patients with unilateral and bilateral vestibular deficits often use saccadic eye movements to compensate for an inadequate VOR. Two types of compensatory saccades have been distinguished, covert saccades and overt saccades. Covert saccades occur during head rotation, whereas overt saccades occur after the head has stopped moving. The generation of covert saccades is part of a central vestibular compensation process that improves visual acuity and suppresses oscillopsia. Understanding the covert saccade mechanism may facilitate vestibular rehabilitation strategies that can improve the patient’s quality of life. To understand the brain mechanisms underlying covert saccades at the neural level, studies in an animal model are necessary. In this study, we employed non-human primates whose vestibular end organs are injured. Methods We examined eye movement during the head-impulse test, which is a clinical test to evaluate the vestibulo-ocular reflex. During this test, the monkeys are required to fixate on a target and the head is rapidly and unexpectedly rotated to stimulate the horizontal semi-circular canals. Results Similar to human subjects, monkeys made compensatory saccades. We compared these saccades with catch-up saccades following a moving target that simulates the visual conditions during the head impulse test. The shortest latency of the catch-up saccades was 250 ms, which indicates that it requires at least 250 ms to induce saccades by a visual signal. The latency of some compensatory saccades is shorter than 250 ms during the head impulse test, suggesting that such short latency compensatory saccades were not induced visually. The peak velocity of the short latency saccades was significantly lower than that of longer latency saccades. The peak velocity of these longer latency saccades was closer to that of visually guided saccades induced by a stepping target. Conclusion These results are consistent with studies in human patients. Thus, this study demonstrates, for the first time, compensatory covert saccades in vestibular impaired monkeys.